The donor line break cannula: effect on the donation process, blood component quality and transfusion microbiology testing of an important new blood bag safety feature. Issue 4 (5th May 2013) - Nightingale, M. J.; Beard, M. J.; Bennett, J.; Hambleton, R.; Ramskill, S.; Thomas, S.
SUMMARY: Background: The use of blood packs with an integral sampling system can result in anti‐coagulant from the main bag reaching the sample pouch via the donor line, causing delayed coagulation of blood samples. In NHS Blood and Transplant, this has prevented the use of serum, the preferred matrix for transfusion microbiology (TM) testing, which has led to an increased false positive rate with ethylenediaminetetraacetic acid (EDTA) plasma. There is also a remote possibility of false negative results owing to sample dilution. Manufacturers have responded by offering packs with a donor line break cannula (DLBC) to prevent these adverse effects. Objectives: The aims of this study were to assess the impact of DLBC packs on donation, blood component quality and of the potential return to serum for TM testing. Methods: DLBC packs from three manufacturers were assessed against control packs of the same dimensions and configuration. Donation duration, flow rate, platelet factor 4, prothrombin fragment 1+2, haemolysis and collection and processing incidents were compared. Results: Results indicated no clinically significant adverse effect from the DLBC on the activation state of platelets, the coagulation cascade or increased haemolysis. Donation duration and blood collection and processing incident rates for DLBC packs were not significantly different to controls. Conclusions: The use of DLBC packs would reduce the complexity of manipulations during blood collection and therefore the likelihood of microbially contaminated donations (incorrect skin core diversion) and false negative TM tests. DLBC packs would enable the use of serum for TM testing with a significant reduction in false positive tests compared to EDTA plasma.